Strategies for Preserving the Sanctity of Pura Taman Pecampuhan Sala Bangli Amidst the Development of Spiritual Tourism - Ni Wayan Sutariani (Nawasena: Jurnal Ilmiah Pariwisata, 2025)
This study explores strategies for preserving the sanctity of Pura Taman Pecampuhan Sala Bangli amidst the growing development of spiritual tourism. Pura Taman Pecampuhan Sala is a temple in Bali that holds significant historical and spiritual value. The development of tourism, especially spiritual tourism, presents unique challenges in maintaining the temple’s sacredness and authenticity. This research adopts a qualitative approach using case study methods, in-depth interviews, and participatory observation to collect data. The findings reveal several key strategies in preserving the temple’s sanctity. First, strengthening the role of customary laws and local traditions in every religious activity at the temple. Second, implementing strict regulations regarding tourist access and behavior, including restricting certain sacred areas. Third, educating and raising awareness among tourists about the importance of maintaining the temple’s sanctity and understanding its spiritual values. Fourth, establishing collaboration between the government, temple administrators, and local communities to manage and promote spiritual tourism without compromising the temple’s sacredness. Fifth, conducting regular monitoring and evaluation of tourism’s impact on the temple’s sanctity. The study concludes that these strategies are effective in preserving the sanctity of Pura Taman Pecampuhan Sala amidst the pressures of spiritual tourism. However, ongoing efforts and strong commitment from all stakeholders are essential to ensure that the temple’s sacred and spiritual values are sustained and passed on to future generations.